Mapeamento quantitativo da evolução das atividades de extensão universitária, do ensino e da pesquisa realizadas pela Universidade Federal de Lavras no período de 2011 a 2015 - Selvati, Anderson de Oliveira (2016)
The University Extension Program can be an element in the professional constitution of the Brazilian university professor, shaped by an inseparable relationship of the fields of extension, teaching and research. Because of the importance that the balance between these three fields can have on the performance quality of these institutions, this paper proposed to quantify the extension, teaching and research activities developed by the Federal University of Lavras (UFLA), in the period from 2011 to 2015. The methodological procedure was the documentary analysis of the records of these activities in the Pro-Rectories of Extension and Culture, Education and Post-graduation of the institution. The extension actions presented an increase around 9% while the teaching and research actions obtained, each one, an increase around 30% of its activities. Beyond the imbalance of these activities, it was observed the lack of spreadsheets with information needed for more accurate analysis and understanding of these activities, which could encourage and enable advances and improvements in these actions and a possible balance between them. It was concluded that UFLA performs university extension, teaching and research activities, but with a greater appreciation for teaching and research activities and with less consideration of the extension activities.